2014
DOI: 10.1007/430_2014_140
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Formation, Structure and Reactivity of Gold Cluster Ions

Abstract: With the advent of electrospray ionisation (ESI) and matrix-assisted laser desorption ionisation (MALDI), mass spectrometry (MS) is now routinely used to establish the molecular formulae of gold nanoclusters (AuNCs). ESI-MS has been used to monitor the solution phase growth of AuNCs when gold salts are reduced in the presence of phosphine or thiolate ligands. Beyond this analytical role, over the past 2 decades MS-based methods have been employed to examine the fundamental properties and reactivities of AuNC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 373 publications
(472 reference statements)
0
2
0
Order By: Relevance
“…Oxide‐supported gold nanoparticles catalyze a variety of reactions, and recent work has been focused on the potential of these catalysts to react with SO 2 , as well as to understand how SO 2 can hinder the ability of the catalysts to perform other reactions . Attempts have also been made to gain a more basic understanding of the catalytic activity by relating the reactivity of gas‐phase gold clusters to that of the supported gold catalysts . Previous studies with gas‐phase gold clusters have shown that the global charge is related to the adsorption ability, with anions showing particularly interesting activity .…”
Section: Introductionmentioning
confidence: 99%
“…Oxide‐supported gold nanoparticles catalyze a variety of reactions, and recent work has been focused on the potential of these catalysts to react with SO 2 , as well as to understand how SO 2 can hinder the ability of the catalysts to perform other reactions . Attempts have also been made to gain a more basic understanding of the catalytic activity by relating the reactivity of gas‐phase gold clusters to that of the supported gold catalysts . Previous studies with gas‐phase gold clusters have shown that the global charge is related to the adsorption ability, with anions showing particularly interesting activity .…”
Section: Introductionmentioning
confidence: 99%
“…The literature about coinage metal (Cu, Ag, Au) clusters reacting with O 2 (and other molecules) has been evaluated several times more recently. 11 d ,29 d – f ,252 Anionic coinage clusters exhibit a pronounced odd/even oscillation of the reaction rate that is anti-correlated with the electron binding energies of the clusters. The even-numbered coinage cluster anions M 2 n − are open-shell due to the d 10 s 1 atomic configurations and typically show lower electron binding energies than their neighboring sizes.…”
Section: Probing Ligand Binding and Chemistry On Metal Clustersmentioning
confidence: 99%